Unveiling the Etiology of Urological Tumors: A Systematic Review of Mendelian Randomization Applications in Renal Cell Carcinoma, Bladder Cancer, and Prostate Cancer - Tang, Zhicheng; Can, Liu; Xuan, Sun; Chen, Lihui; Zhang, Jiahao; Zhang, Binghua; Wan, Xitong; Li, Zhibiao; Tang, Fucai; He, Zhaohui (Urology Journal, 2024)
Background: Our study aims to address two pivotal questions: "What are the recent advancements in understanding the etiology of urological tumors through Mendelian Randomization?" and "How can Mendelian Randomization be more effectively applied in clinical settings to enhance patient health outcomes in the future?" Methods: In our systematic review conducted in April 2023, we utilized databases like PubMed and Web of Science to explore the influence of Mendelian Randomization in urological oncological diseases. We focused on studies published from January 2018, employing keywords related to urological tumors and Mendelian Randomization, supplemented with MeSH terms and manual reference checks. Our inclusion criteria targeted original research studies, while we excluded reports and non-relevant articles. Data extraction followed a PICO-based approach, and bias risk was independently evaluated, with discrepancies resolved through discussion. This systematic approach adhered to PRISMA guidelines for accuracy and thoroughness in reporting. Results: From the initial 457 publications, we narrowed down to 43 full-text articles after screening and quality assessments. A deeper understanding of Mendelian Randomization can help us explore risk factors with a clear causal relationship to urological tumors. This insight may pave the way for future research in early diagnosis, treatment, and management of associated diseases. Conclusion: Our review underscores the value of MR in urogenital tumor research, highlighting its efficacy in establishing causality and its potential to clarify disease mechanisms. Despite challenges like large sample sizes and variant identification, MR offers new perspectives for understanding and managing these tumors, suggesting a trend towards more inclusive and diverse research approaches.